Єврейське питання в політиці урядів міжвоєнної Польщі - Крамар, Юрій Вікторович; Kramar, Yurij (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкрито характер та зміст державної політики щодо єврейського населення міжвоєнної Польщі. Проаналізовано плани й програми польських урядових кіл у вирішенні єврейського питання. Значну увагу приділено аналізу законодавчих документів, які регулювали діяльність єврейських віросповідних громад у Другій Польській Республіці. The article shows the character and content of the state policy as to the Jewish population of interwar Poland. Plans and programs of Polish governmental surroundings in the decision of the Jewish question are analysed in the article. Here we can see that the article draws a conclusion that policy of Polish government as to Jewish people was not consistent. It balanced on the limit between the attemts to regulate Polish-Jewish relations on the political basis of (the Agreement in 1925) to introduction as to Jewish people frankly discriminatory limitations inthe sphere of culture, education and afterwards in the sphere ofeconomics. In the second halfof1930 th an anti-semitism began to play a greater role in the state policy of Polish government. On the eve oftheSecond World Warthe priority direction todecidethe Jewish question in Polandwas determined as Jewish emigrationfrom the country.
The Jewish Question in the Policy of governments of Interwar Poland
Keywords: польська державна політика; національне питання; євреї; конфесійна громада; польсько- єврейські відносини; Polish state policy; national question; Jewish; confessional community; Polish-Jewish relations